Integration technology for local energy internet - Shuquan LI; Siwei LI; Shihai YANG; Xiaodan LIU; Liang YUE (Dianxin kexue)
The overall design ideas and system integration ideas of local energy internet were introduced.In view of the system integration technology,the local energy internet was explored and studied from three aspects of planning and terminal access integration,equipment and system integration,integration between different systems.The achievements were practiced in the State Grid Customer Service Center Northern Park.Practice results show that local energy internet can convert electrical energy and other clean energy into the cold,heat,electricity and other energy required by the region.The effective integration of energy flow and data flow,complementary advantages,interconnection and sharing among the each energy sources is achieved.